Técnicas de biologia molecular para ceratites infecciosas - Salomão, Heloisa Moraes do Nascimento [UNIFESP] (2017)
Objectives: To study the conjunctival microbiota and etiologic diagnosis in patients with infectious keratitis due to alpha Herpes virus and Mycobacteria with molecular biology techniques. Methods: Conjunctival microbiota analysis was performed in ocular surface samples in eyes previously submitted to Boston Type I keratoprosthesis surgery with PCR assay with amplicon analysis using electrospray ionization mass spectroscopy (PCR/ESI-MS). To study corneal viral infections real-time PCR was used for Herpes Virus Type 1 and 2 (HSV 1 and 2) and Varicella Zoster Virus in corneal scrapings from typical herpes dendritic keratitis and from the corneal stroma of patients with unspecific infectious keratitis. Polymerase chain reaction–restriction enzyme analysis of the hsp65 gene (PRA-hsp65), DNA sequencing and pulsed-field gel electrophoresis were used to identify Mycobacteria strains isolated in corneal samples of a post-refractive surgery infection outbreak. The same methodology was used to study samples of tap and distilled water, water from the reservoir of the distilling equipment, steamer, and autoclave cassette; antiseptic and anesthetic solutions and surgical instruments. Results: The molecular diagnostic approach using serial polymerase chain reaction and mass spectrometry was comparable with standard microbiologic techniques as a surveillance tool in patients previously submitted to Boston type I keratoprosthesis implantation. Of the 25 patients in the dendritic keratitis group, 21 tested positive for HSV-1 by qPCR analysis. From the unspecific keratitis group (65), nine patients had negative smears, cultures, and qPCR findings. Fifty-six patients had positive cultures: 51 for bacteria, 4 for fungi, and 1 for amoebae. From those, qPCR identified 10 patients who were also positive for virus: one for VZV and nine for HSV-1. Polymerase chain reaction–restriction enzyme analysis of the hsp65 gene (PRA-hsp65), DNA sequencing and pulsed-field gel electrophoresis were used to identify Mycobacteria in eyes with clinical signs of infection. The same strain isolated from the patient’s eyes was obtained in tap distilled water samples, which suggests that the contamination source could have been the distilled water used to rinse the instruments. Conclusion: PCR/ESI-MS is comparable to cultures to study conjunctival microbiota and is a possibility of post-operative follow-up. Real-time PCR was able to demonstrate Herpes Virus in typical cases of Herpes keratitis and in unspecific keratitis initially suspicious of bacteria, suggesting mist infection. Polymerase chain reaction–restriction enzyme analysis of the hsp65 gene (PRA-hsp65), DNA sequencing and pulsed-field gel electrophoresis were important to identify Mycobacteria in a post-refractive surgery Mycobacterium chelonae outbreak. Molecular Biology can be used to investigate ocular infections bringing new insights that contribute to comprehension and correlation of infectious processes.